ASSESSMENT OF BASIC FEASIBILITY AND FINANCIAL ANALYSIS OF SIOMAI PRODUCTS PRODUCED BY SMALL AND MEDIUM-SIZED ENTERPRISES - Sakiba, Syakira Nazma; anasri, Anasri; Panjaitan, Pola Sabar Tomohon; Ningih, Trisna; Hasanah, Haliza Nurul; Napitupulu, Romauli Juliana (Politeknik Kelautan dan Perikanan Karawang, 2026)
Fish siomay made from white snapper (Lates calcarifer) and swanggi fish (Priacanthus tayenus) represents a processed seafood product with promising business potential. This study aims to evaluate the implementation of basic feasibility requirements and financial analysis for fish siomay produced by small- and medium-sized enterprises (SMEs). Data were collected through direct observation, interviews, and surveys involving two siomay SMEs. Compliance with the basic feasibility clauses of the SMEs Processing Feasibility Certificate (SKP) was assessed using a gap analysis method, while financial feasibility was examined through calculations of investment cost, production cost, profit, break-even point (BEP), benefit–cost ratio (B/C ratio), cost of goods sold (COGS), and yield. The research results indicate that Siomay Micro, Small, and Medium Enterprises (MSMEs) processing Siomay made from snapper fish have an average compliance level of 94.56% with an average gap level of 5.44%, while MSMEs using swanggi fish have an average compliance level of 90.82% with an average gap level of 9.18%. Thus, both MSMEs are considered capable of meeting the standards for implementing basic feasibility In financial terms, the production of swanggi-fish siomay generated a monthly profit of IDR 2,375,074, with a COGS of IDR 15,848, an investment cost of IDR 37,257,000, a production cost of IDR 9,064,926, a BEP of 388 packs, and a B/C ratio of 1.3. Meanwhile, white snapper siomay production yielded a monthly profit of IDR 6,467,460, with a COGS of IDR 9,708, an investment cost of IDR 26,996,000, a production cost of IDR 7,572,540, a BEP of 293 packs, and a B/C ratio of 2. SMEs X has a yield of 125.41%, while SMEs Y has a yield of 114.28%. Thus, the yield results indicate that SMEs X is greater than SMEs Y. This difference is attributed to the addition of Isolated Soya Protein (ISP) to the fish siomay at SMEs X. The fact that the yield results from both SMEs exceeded 100% is due to the inclusion of dumpling wrappers and other ingredients. Overall, both SMEs met the basic feasibility requirements of the production process and demonstrated positive financial prospects, although white snapper-based siomay showed better performance in both process compliance and economic efficiency